Simon Grennan & Christopher Sperandio : Life in Prison. - Eastern State Penitentiary Philadelphia (Seattle : Fantagraphics Books, 1995)
Life in Prison was produced as an artwork for Prison Sentences : The Prison as Site / The Prison as Subject, an exhibition of site specific artworks at Eastern State Penitentiary in Philadelphia (Pennsylvania).
Engels
Simon Grennan & Christopher Sperandio, Life in Prison : Simon Grennan, Christopher Sperandio, Eastern State Penitentiary Philadelphia, 1995-05
boek
Keywords: Grennan, Simon; Sperandio, Christopher; Grennan & Sperandio